Pengaruh Kepemilikan Institusional, Komisaris Independen, dan Komite Audit pada Penghindaran Pajak Perusahaan - Alif Hakim; Royhisar Martahan Simanungkalit (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine the effect of Institutional Ownership, Independent Commissioners, and Audit Committees partially on Tax Avoidance. The approach to this study is quantitative. This study uses data from companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 - 2023 which are on the Main Listing Board in the health sector. Sampling was carried out by purposive sampling with the criteria of routinely reporting annual reports from 2019 - 2023 from health companies with the period January to December. In this study, there were 16 companies that met the sample with a total of 70 observation data. Measurement of Institutional Ownership is by dividing the proportion of shares owned by the number of shares issued. Independent commissioners are measured by calculating independent commissioners by the total number of commissioners. The audit committee is measured by calculating the number of audit committee meetings per year. Tax avoidance is measured using the Effective Tax Rate (ETR) by dividing income tax burden by profit before tax. The inferential analysis technique of this study uses panel data regression analysis technique with the help of Eviews 12 statistical application. The results of the study indicate that Institutional Ownership has no effect on Tax Avoidance, so the first hypothesis is not proven. The proportion of Independent Commissioners has no effect on Tax Avoidance, so the second hypothesis is not proven. The Audit Committee has no effect on Tax Avoidance, so the third hypothesis is not proven.